Avaliação de usabilidade de um software de monitoramento: sistema orientado ao monitoramento de ativos de engenharia - Sefrin, Yuri Fernando Tiecher (2021)
The evaluation of software usability is an important topic for a society. Usability relies on factors intrinsic to the task to be performed. In hydroelectric plants the main task to be performed by operators is the analysis and monitoring of the sensors of the generating unit. The hypothesis is that the use of a 3D interface brings more usability and efficiency to find the sensors. The work applies Nielsen's heuristics to ensure good usability. In addition, the work defines the tasks for applying the usability test through interviews and verifies that the hypothesis is valid for the execution of several tasks of the day-to-day of the engineer. The results obtained with the heuristic analysis directly impacted the development of new features that allow engineers and technicians to perform the activity of monitoring signals from sensors more easily compared to conventional techniques.